Assessing The Effectiveness Of Vaccination Campaigns In Controlling Infectious Diseases - Burak Kay; Serkan Demir; Leyla Çelik (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This article assesses the effectiveness of vaccination campaigns in controlling the spread of infectious diseases, focusing on recent outbreaks of measles and influenza. Through a comparative analysis of vaccination rates and disease incidence in different regions, the study identifies key factors contributing to successful vaccination efforts. The findings emphasize the importance of public awareness and accessibility in achieving high vaccination coverage to prevent outbreaks.